KENDALA BAHASA DALAM MEMPROMOSIKAN MARISA BEACH-TEMPAT WISATA DI NIAS UTARA - Hulu, Nesti Arni; Zega, Noniat; Zai, Peristiwa Diken Kasatria; Harefa, Afore Tahir (Jurnal Internasional Riset Bisnis Pariwisata, 2024)
The study investigates the language constraints faced by the community around Marisa Beach at Nias Utara, Indonesia, which prevent them from effectively promoting and developing the tourist destination in their area. Marisa Beach is a popular tourist destination, but it currently lacks visitors due to inadequate promotion by the local community. The research focuses on identifying the key language-related challenges that hinder the community's ability to promote their tourist destination. The literature review highlights the importance of community involvement in tourism development and the language barriers that can impede such participation. The findings of this study are expected to provide insights into the language-related challenges that communities face in promoting tourism. The researchers aim to understand the specific difficulties the Marisa Beach community experiences in terms of promotional language, communication structures, and promoting knowledge. The study's conclusions may inform strategies to support the community in overcoming these language constraints and actively participating in the development and promotion of their local tourist destination.